Hubungan jarak kelahiran dan jumlah balita dengan dengan status gizi balita di Puskesmas Sapta Jaya, Aceh Tamiang - Kasad Kasad; Keumalahayati Keumalahayati (Jurnal SAGO Gizi dan Kesehatan, 2020)
Background: Indonesia ranks fifth for the country with the number of stunted children with an estimated 7.7 million children under five. Globally, WHO states that around 45% of under-five mortality is due to malnutrition and Indonesia has undernutrition problems that cannot be resolved. The factors causing the high nutritional problems include the number of children under five in the family and the support of the close distance between the births of the babies.Objectives: To measure the relationship between birth spacing and the number of children under five with the nutritional status of children under five at the Sapta Jaya Health Center, Aceh Tamiang.Methods: This study was used a cross-sectional design. The sample size as many as 31 people, using the sampling technique by simple random sampling. The data collection technique used a questionnaire and conducted interviews, as well as anthropometric measurements of weight for age to assess nutritional status. Statistical analysis used the Chi-Square test at a significance level of 95%.Results: There is a number of children under five who experience malnutrition, namely 25.8%. The number of children under five in the family had no relationship with the nutritional status of children under five (p= 0.952), while the birth spacing had a relationship with the nutritional status of children under five at the Sapta Jaya Community Health Center, Aceh Tamiang (p= 0.031). Conclusion: The number of children under five has no relationship with nutritional status, but birth spacing has a significant relationship with the nutritional status of children under five.